Curricular Units: Powerful Tools to Connect the Syllabus with Students' Needs and Interests - Ariza Ariza Aleida (Universidad Nacional de Colombia, 2004)
A basic component of any language program is the construction of the curriculum. There is a variety of approaches to curriculum planning and implementation from the technical production perspective to the critical view. The current article emerged from the analysis of the syllabus in a Basic English course in the undergraduate program at Universidad Nacional de Colombia and the design and implementation of a curricular unit. Such unit proved to be a powerful tool to connect what was set in the program, what students needed in terms of language and what they were interested in terms of culture. Key words: Curriculum, Curricular Unit Platform, Constructivism, Teaching- Communicative Language, Task-Based Approach Un componente esencial en un programa de idiomas es la construcción del currículo. Existe una gran variedad de enfoques en términos del diseño y la implementación del currículo; desde una perspectiva reducida a la producción técnica, hasta una visión crítica y transformadora. El presente artículo se gesta a partir tanto del análisis de un programa correspondiente al curso Inglés Básico I en la licenciatura ofrecida por la Universidad Nacional de Colombia, como del diseño y la implementación de una unidad curricular. Dicha unidad curricular se caracterizó por convertirse en una herramienta de conexión entre los contenidos y procedimientos planteados en un programa y las necesidades comunicativas e intereses culturales de los estudiantes. Palabras claves: Currículo, Plataforma Curricular, Unidad Curricular, Constructivismo, Lenguas Extranjeras-Enseñanza Comunicativa, Enfoque basado en Tareas